PARTISIPASI POLITIK PEMILIH PEMULA PADA PEMILIHAN UMUM TAHUN 2019 (Studi Kasus di Desa Botubilotahu Kecamatan Marisa Kabupaten Pohuwato) - Iskandar Ibrahim (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2022)
This study aims to determine the political participation of first-time voters in the 2019 elections in Botubilotahu Village, Marisa District, Pohuwato Regency. This research is a qualitative research with descriptive analysis method. The data in this study were obtained from interviews with 10 first-time voters in Botubilotahu Village, Marisa District. Furthermore, the data were analyzed using three paths of data analysis developed by Miles and Huberman. The results of this study indicate that the political participation of young voters in Botubilotahu Village, Marisa District has increased. Forms of political activity carried out by first-time voters in Botubilotahu Village, Marisa District were in the form of voting, campaigns, members of democracy volunteers, and demonstrations. Based on their liveliness and activities, they can be categorized into types of Spector political participation, Gladiator political participation, and Critical political participation. In this study, it was also found that factors influencing the political participation of first-time voters were information disclosure or political stimulus, social characteristics, the political system in the area of residence, and regional differences.